Irish peasants : violence & political unrest, 1780-1914 - Clark, Samuel, 1945-; Donnelly, James S. (UPCC book collections on Project MUSE., 1983)
"The strength of this volume cannot be conveyed by an itemisation of its contents; for what it provides is an incisive commentary on the newly-recognised landmarks of Irish agrarian history in the modern period. ... The importance, even indispensability, of this achievement is compounded by exemplary editing."--Roy Foster, London Times Literary Supplement "As a whole, the volume demonstrates the wealth, complexity, and sophistication of Irish rural studies. The book is essential reading for anyone involved in modern Irish history. It will also serve as an excellent introduction to this rich field for scholars of other peasant communities and all interested in problems of economic and political developments."--American Historical Review "A milestone in the evolution of Irish social history. There is a remarkable consistency of style and standard in the essays. ... This is truly history from the grassroots."-Timothy P. O'Neill, Studia Hibernica.